2018
DOI: 10.5812/ijp.64087
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Head and Neck Masses in Iranian Children During a 21-Year Period

Abstract: Background: Head and neck masses are common in infants, children and adolescents. Etiologically, these masses are divided into three groups of inflammatory, congenital and neoplastic lesions. Their incidence rate has been variable in different parts of the world. This study aimed to determine the frequency of head and neck masses in Iranian children during a 21-year period. Methods: This retrospective, descriptive study was performed on medical files of patients between 2 to 12 years with pathological head and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Khiavi et al,5 observed that head and neck masses are common in infants, children, and adolescents. Of 594 children, 63.3% were males and 36.7% were females (maleto-female ratio of 1.7:1, P<0.001).…”
mentioning
confidence: 99%
“…Khiavi et al,5 observed that head and neck masses are common in infants, children, and adolescents. Of 594 children, 63.3% were males and 36.7% were females (maleto-female ratio of 1.7:1, P<0.001).…”
mentioning
confidence: 99%